The role of forgiveness in mediating the relationship between emotion regulation and subjective well-being of students - Siti Hikmah; Mungin Edy Wibowo; Mulawarman Mulawarman; Sunawan Sunawan; Paola Colonello (Faculty of Psychology and Health - Universitas Islam Negeri Walisongo Semarang, 2025)
University students frequently encounter academic pressures and emotional challenges that affect their subjective well-being. Emotion regulation is therefore an essential competency, while forgiveness is understood as a psychological mechanism that can mediate emotion regulation's influence on well-being. This study investigates the mediating roles of forgiveness in the relationship between emotion regulation and subjective well-being among Indonesian university students. Using a quantitative design, 1,790 participants from multiple universities were recruited through convenience sampling. The instruments employed measured emotion regulation, forgiveness, and subjective well-being. Path analysis demonstrated that forgiveness functioned as a significant mediator between emotion regulation and subjective well-being (β = .521, p < .001). Forgiveness was included in the model, the direct effect of emotion regulation on subjective well-being became non-significant (β = −.023, p = .285), indicating a full mediation effect. These results underscore the importance of promoting forgiveness, suggesting that universities should incorporate counseling and reflective programs grounded in forgiveness to enhance students' emotion regulation and subjective well-being.